Fabrication of rice husk-mycelium biocomposite as alternative to polystyrene packaging - Arazas, Andrea Pauline R.; Potestades, Maria Lourdes P.
Petroleum-based polymer, specifically polystyrene, is commonly used for packaging applications worldwide. However, these petroleum-based polymers are non-biodegradable, which imposes great issues in our environment. This study aims to fabricate a biocomposite alternative to polystyrene in packaging that is composed of locally-available rice husk and mycelium from mushrooms. The rice husks and other materials in contact with the mycelium werefirst sterilized using an autoclave for 1 hour at 15 psi. The components were combined in a blender at different rice husk-mushroom ratio and then transferred into difterent metal molds. After 5 days, the samples were removed from the mold and then subjected to a Universal Testing Machine fo r compres ion and flexure test. Also, they were put under a Scanning Electron Microscope to analyze their morphologies. It was observed that the ratio with the maximum strength as compared to the polystyrene was with 100% mycelium (0.219Mpa vs. 0.110Mpa for flexure and 2.647Mpa vs. 0.345Mpa for compression). Furthermore, the compressive and flexural strengths were seen to be both directly proportional to the amount of mycelium present in the composite. SEM images showed the networks of mycelium around the rice husks. In conclusion, it can be inferred that it is feasible to fabricate a Polystyrene alternative by combining locally-available mycelium and rice husk. The mechanical properties of the biocomposite well exceeded that of Polystyrene, making it promising not only for packaging, but also for applications requiring higher flexural and compressive strengths.